Extraction of nanostructured sodium nitrate from industrial effluent and their thermal properties. (22nd April 2020) - Yadav, Krishna K.; Sharma, Manu; Jha, Menaka
Abstract: This study describes a process of extraction of high purity sodium nitrate from corrosive chemical industry effluents. Here, we have designed a process to convert highly corrosive effluents of ceramic industries having pH 13.1 into sodium nitrate nanoparticles. The extraction of sodium nitrate has been carried out via neutralization of industrial effluent by nitric acid. We have also studied the effect of low boiling point co‐solvent during recrystallization of sodium nitrate. TEM studies of sodium nitrate extracted from the filtrate in the absence of co‐solvent show the formation of nanoparticle of 70 nm. Further, a drastic decrease in particle size to 10 nm has been observed when co‐solvents (methanol, ethanol, and acetone) were used in combination with filtrate during the recrystallization process of sodium nitrate. Thermal properties of sodium nitrate extracted from filtrate have been investigated. Our result indicates that the nanoparticles extracted from filtrate having very high heat storage density (453 J/g) without hampering the melting point and boiling point of the materials. Practitioner points: The new chemical process has been developed to treat the industrial effluent Extraction of nanostructured sodium nitrate has been carried from industrial effluent The particle size of sodium nitrate drastically influenced by the used co‐solvent for recrystallization The highest heat storage density is 453 J/g, which was obtained from the recrystallization of the filtrate Abstract : Conversion of corrosive industrial effluent into sodium nitrate nanostructures and their application in heat storage.